تأثير زاوية انحراف الموجة فوق الصّوتيّة على نمط التّداخل وعامل الجودة للمرشّحات فوق الصّوتيّة - الضّوئيّة المولّفة - جنيكه فرح (Latakia University Journal -Engineering Sciences Series, 2017)
تعدّ المرشّحات فوق الصّوتيّة-الضّوئيّة المعتمدة على تقنيّة التّداخل بين الأمواج فوق الصّوتيّة والضّوئيّة مرشّحات عالية الأداء، حيث أنّها تملك مجال انتخابي هو الأكبر مقارنة مع الأنواع الأخرى من المرشّحات وهذا مايتيح استخدامها في شبكات التّجميع بتقسيم طول الموجة(WDM: Wavelength Division Multiplexing) البصرية، ويهدف البحث إلى دراسة نموذجين لهذه المرشّحات أحدهما يعمل وفق نمط التّداخل غير المتوازي والآخر يعمل وفق نمط التّداخل شبه المتوازي وذلك بهدف المقارنة بينهما من الناحية العمليّة. يهدف البحث إلى إظهار تأثير زاوية الانحراف للموجة فوق الصّوتيّة على تصميم المرشّح وفعاليته في انتخاب طول الموجة الضّوئيّة المرغوب بالإضافة إلى مقارنة منحنيات التّردد الموافقة لهذه الزوايا من حيث حساسيتها لتغيرات زاوية الورود، كما تكمن أهمية البحث في إثبات فعالية المرشّحات التي تعمل وفق النّمط شبه المتوازي للتّداخل وقدرتها على تحقيق القيم العالية جداً لعامل الجودة. The acousto-optic filters that depend on the interaction technology between the optical and ultrasonic waves are considered a high- performance filters as they have the largest tuning range compared to other filters types. These filters can be used in optical WDM (Wavelength Division Multiplexing) networks. This work aims to study two types of these filters, one operates according to the non-collinear type of interaction, whereas the other type operates according to the quasi-collinear type of interaction, and compare between these two filters types from the practical side. Thus, this work aims to show the tilt angle effect of the acoustic wave on the filter’s design and its efficiency in electing the desired optical wave length, in addition to compare the frequency curves related to these angles in terms of their sensitivity to the changes of the incidence angle. The importance of this work lies in proving the efficiency of the filters operating according to the quasi-collinear type of interaction and their ability to achieve the high values of quality factor.